ANALYSIS OF TOURISM COMPETITIVENESS POTENTIAL IN LABOUR ABSORPTION IN WEST SUMATRA - Yusuf, Muhammad; Satrianto, Alpon (Jurnal Ilmiah Ekonomi Bisnis, 2025)
This study aims to determine the competitiveness of tourism sector employment in West Sumatra Province and to determine how much the ability of the tourism sector in creating employment opportunities due to national economic growth. The data used is secondary data sourced from BPS West Sumatra Province. The method used in the research is Shift-Share Analysis and Locatio Quotient (LQ) analysis. This study concludes that the tourism sector of West Sumatra Province is able to create employment opportunities due to the growth of employment opportunities in national, which is indicated by the large number of employment in the tourism sector. The growth of the tourism sector in West Sumatra Province will affect the total growth of the tourism sector in Indonesia. Which shows a positive value means that there is growth in the in the sector due to the influence of the growth of the reference region sector. The West Sumatra Province tourism sector has good growth by having a competitive advantage but not specialised. The development of West Sumatra province must be done by spurring the performance of the tourism sector so that it can grow rapidly and make a large contribution to GRDP growth and employment.